1993
DOI: 10.1093/nar/21.17.4085
|View full text |Cite
|
Sign up to set email alerts
|

Purification and cDNA cloning of HeLa cell p54nrb, a nuclear protein with two RNA recognition motifs and extensive homology to human splicing factor PSF andDrosophilaNONA/BJ6

Abstract: While searching for a human homolog of the S.cerevisiae splicing factor PRP18, we found a polypeptide that reacted strongly with antibodies against PRP18. We purified this polypeptide from HeLa cells using a Western blot assay, and named it p54nrb (for nuclear RNA-binding protein, 54 kDa). cDNAs encoding p54nrb were cloned with probes derived from partial sequence of the purified protein. These cDNAs have identical coding sequences but differ as a result of alternative splicing in the 5' untranslated region. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
145
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 42 publications
0
145
0
1
Order By: Relevance
“…10 and references therein), and the conformational state of the actin involved in transcription remains to be investigated. Hrp65 belongs to a family of evolutionarily conserved proteins characterized by the presence of a DBHS domain (27). The DBHS group includes the mammalian proteins PSF, p54 nrb ͞ NonO, and PSP1 and the Drosophila protein NonA͞Bj6 (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…10 and references therein), and the conformational state of the actin involved in transcription remains to be investigated. Hrp65 belongs to a family of evolutionarily conserved proteins characterized by the presence of a DBHS domain (27). The DBHS group includes the mammalian proteins PSF, p54 nrb ͞ NonO, and PSP1 and the Drosophila protein NonA͞Bj6 (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…For both 5' and 3'-RACE, sequences were obtained that diverged from known TFE3 sequences at the exon 3-exon 4 junction (eg, the 5'-RACE product is shown in Figure 2b). Database searches of the new sequences present in the 5'-RACE and 3'-RACE products revealed that they exactly matched adjacent regions of a gene designated NonO (p54 nrb ) that is closely related to PSF (Dong et al, 1993;Yang et al, 1993). The 471 amino acid NonO (p54 nrb ) protein contains several distinct domains ( Figure 3) including (i) a short N-terminal sequence composed entirely of histidine, glutamine and proline residues, (ii) a helix ± turn ± helix domain¯anked by charged amino acids that is responsible for binding to the octamer sequence in double stranded DNA and (iii) a short C-terminal proline-rich region.…”
Section: Fusion To the Psf Gene In Uok145mentioning
confidence: 98%
“…The 471 amino acid NonO (p54 nrb ) protein contains several distinct domains ( Figure 3) including (i) a short N-terminal sequence composed entirely of histidine, glutamine and proline residues, (ii) a helix ± turn ± helix domain¯anked by charged amino acids that is responsible for binding to the octamer sequence in double stranded DNA and (iii) a short C-terminal proline-rich region. The NonO (p54 nrb ) protein has a region of 320 amino acids with 71% identity and 7% similarity to a 320aa region of PSF (Patton et al, 1993;Dong et al, 1993;Yang et al, 1993). This same region of NonO (p54 nrb ) exhibits 42% identity and 7% similarity to a 321aa region of the 700aa Drosophila NonA diss protein.…”
Section: Fusion To the Psf Gene In Uok145mentioning
confidence: 99%
“…14,[16][17][18][19][20][21][22][23] It is comprised of an N-terminal glycine-rich domain, a proline/glutamine (P/Q) rich domain, two RNA recognition motifs (RRMs), and a C-terminal region with two nuclear localization signals. A closely related protein with a similar domain structure, p54 nrb (and its mouse homolog nonO) 24,25 has been found to associate with PSF. 23,[26][27][28] Together, these proteins interact with the C-terminal domain (CTD) of RNA Pol II 29 and contact 5' splice sites within large transcription/splicing complexes, 30 consistent with coupling between transcription and splicing.…”
Section: Introductionmentioning
confidence: 99%